Targeting spike protein-induced TLR/NET axis by COVID-19 therapeutic NRICM102 ameliorates pulmonary embolism and fibrosis. (October 2022) - Wei, Wen-Chi; Liaw, Chia-Ching; Tsai, Keng-Chang; Chiou, Chun-Tang; Tseng, Yu-Hwei; Chiou, Wen-Fei; Lin, Yu-Chi; Tsai, Chia-I; Lin, Chen-Shien; Lin, Chen-Sung; Liou, Kuo-Tong; Yu, I-Shing; et al.
Abstract: The global COVID-19 pandemic remains a critical public health threat, as existing vaccines and drugs appear insufficient to halt the rapid transmission. During an outbreak from May to August 2021 in Taiwan, patients with severe COVID-19 were administered NRICM102, which was a traditional Chinese medicine (TCM) formula developed based on its predecessor NRICM101 approved for treating mild cases. This study aimed to explore the mechanism of NRICM102 in ameliorating severe COVID-19-related embolic and fibrotic pulmonary injury. NRICM102 was found to disrupt spike protein/ACE2 interaction, 3CL protease activity, reduce activation of neutrophils, monocytes and expression of cytokines (TNF-α, IL-1β, IL-6, IL-8), chemokines (MCP-1, MIP-1, RANTES) and proinflammatory receptor (TLR4). NRICM102 also inhibited the spread of virus and progression to embolic and fibrotic pulmonary injury through reducing prothrombotic (vWF, PAI-1, NET) and fibrotic (c-Kit, SCF) factors, and reducing alveolar type I (AT1) and type II (AT2) cell apoptosis. NRICM102 may exhibit its protective capability via regulation of TLRs, JAK/STAT, PI3K/AKT, and NET signaling pathways. The study demonstrates the ability of NRICM102 to ameliorate severe COVID-19-related embolic and fibrotic pulmonary injury in vitro and in vivo and elucidates the underlying mechanisms. Graphical Abstract: ga1 Highlights: Effective intervention is urgently needed for severe COVID-19 patients at higher risks of fatal pulmonary complications. NRICM102 significantly ameliorates severe COVID-19-related embolic and fibrotic pulmonary injury in vitro and in vivo. NRICM102 exhibits its therapeutic properties via regulation of TLR/NET axis signaling pathways.